1,25-dihydroxyvitamin D3 inhibits corneal wound healing in an ex-vivo mouse model - Sel, Saadettin; Trau, Stefanie; Paulsen, Friedrich; Kalinski, Thomas; Stangl, Gabriele I.; Nass, Norbert (Graefes Archive For Clinical and Experimental Ophthalmology, 2016)
PURPOSE: Impaired healing of corneal injuries can result in ulceration and complete loss of vision, especially in the elderly. Such patients frequently also exhibit vitamin D insufficiency. 1,25-dihydroxyvitamin D3 is the active vitamin D metabolite. As it affects cell proliferation and inflammation, we herein aimed at elucidating its influence on corneal wound healing after alkali burn by using in vitro and ex vivo techniques. METHODS: mRNA abundance in human corneal epithelial cells in response to vitamin D3 was determined by RT-PCR. Corneal re-epithelialization after alkaline burn was analyzed using enucleated mouse eyes and fluorescein staining. RESULTS: Human corneal epithelial cells (HCEC) expressed the vitamin D receptor (VDR) and retinoid x receptor (RXR) and were responsive to 1,25- dihydroxyvitamin D3, as shown by induction of the 1,25- dihydroxyvitamin D3 responsive gene cyp-24A1 and slightly reduced abundance of IL-6 mRNA. However, no effect on cell vitality and migration was observed. In contrast, re-epithelialization of mouse corneas ex vivo was dose dependently inhibited by 1,25- dihydroxyvitamin D3. CONCLUSIONS: These data indicate that topically applied 1,25- dihydroxyvitamin D3 does not seem to be suitable for therapy of corneal lesions.
EVALuna2:35350